Effect of Glycerol Plastic Concentrationon on The Characteristics of Calcium Alginate-Based Edible Film - Jamaran Kaban (Talenta Publisher, 2020)
Calcium alginate-based edible film has been made by way of immersion of sodium alginate into calcium chloride (CaCl2) solution to form calcium alginate gel. In this case, using glycerol is a plasticizer with the variation of concentrations were 0,% 10%, 20%, and 30%. The characterization of edible films has been determined such as thickness, tensile strength, elongation, DTA, SEM, swelling, biodegradable and FT-IR analysis. Edible film characterization showed that with increasing glycerol plasticizer, thickness and tensile strength became greater, while elongation became lower. SEM analysis revealed that surface morphology became smoother and DTA analysis showed greater degradation temperature in the increase of glycerol. Characteristics of swelling showed that edible film without glycerol has to increase in weight with the addition of glycerol. The swelling value increased at the beginning of the measurement but increased after 10 interest. FT-IR analysis revealed that the stretching vibration form of the OH group changed from sharp to broad in the addition of glycerol. The biodegradable result showed an increase in the edible film weight and whole degradation after 21 days.